Association of in vitro fertilization with maternal and perinatal outcomes among pregnant women with active tuberculosis: A retrospective hospital-based cohort study - Xia, Lu; Mijiti, Peierdun; Liu, Xu-Hui; Hu, Zhi-Dong; Fan, Xiao-Yong; Lu, Shui-Hua (Frontiers in Public Health, 2022)
Background Study on effect of fertilization methods on maternal and perinatal outcomes with respect to TB during pregnancy was scarce. This study aimed to analyze maternal and perinatal outcomes in active TB cases after in vitro fertilization (IVF) treatment vs. normal pregnancy. Methods Clinical data of 80 pregnant women with active TB hospitalized at Shanghai Public Health Clinical Center between June 1st, 2014 and November 30th, 2020 were extracted and retrospectively analyzed. History of receiving IVF was recorded at admission and its association with maternal and perinatal outcomes were assessed using multivariable logistic regression models with adjustment for potential confounders. Results Of the 80 pregnant women with active TB, 28 (35.0%) received IVF treatment and 52 (65.0%) did not receive IVF treatment. After adjusting for potential confounders, receiving IVF was associated with worse maternal and perinatal outcomes, including maternal criticality (21.4 vs. 2.0%, adjusted OR = 28.3, P = 0.015), miliary TB (89.3 vs. 13.5%, adjusted OR = 75.4, P < 0.001), TB meningitis (32.1 vs. 7.7%, adjusted OR = 6.2, P = 0.010), and perinatal mortality (64.3 vs. 28.8%, adjusted OR = 9.8, P = 0.001). Conclusion The additional risk of TB to women receiving IVF treatment is a public health challenge specific to countries with a high tuberculosis burden. Increased awareness of latent tuberculosis infection in women receiving IVF treatment is needed.